1988
DOI: 10.1007/bf00612429
|View full text |Cite
|
Sign up to set email alerts
|

Visual optics in toads (Bufo americanus)

Abstract: Aspects of visual optics were investigated in the American toad (Bufo americanus). The development of the refractive state of the eye during metamorphosis was followed with IR photoretinoscopy. Frozen sections documented the changes in optical parameters before and after metamorphosis. There is a difference in light sensitivity between juvenile and adult toads. Binocular accommodation in adult toads was observed. 1. IR photoretinoscopic measurements showed that the refractive state of the eye changed very rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…5C) is slightly higher than the average of the ratio taken from many other vertebrate species (about 0.6; Hughes 1977, p 654). The f/number declines slightly with age, resulting in a 30% brighter image at day 60 than at day 10; this change is less than in the chicken (50 versus 1 day of age: + 49%; Schaeffel et al 1986) or in the toad (adult toad versus tadpole: + 350%; Mathis et al 1988). …”
Section: Schematic Eye Modelling and Calculation Of Image Magnificatimentioning
confidence: 99%
“…5C) is slightly higher than the average of the ratio taken from many other vertebrate species (about 0.6; Hughes 1977, p 654). The f/number declines slightly with age, resulting in a 30% brighter image at day 60 than at day 10; this change is less than in the chicken (50 versus 1 day of age: + 49%; Schaeffel et al 1986) or in the toad (adult toad versus tadpole: + 350%; Mathis et al 1988). …”
Section: Schematic Eye Modelling and Calculation Of Image Magnificatimentioning
confidence: 99%
“…Under natural conditions, adult Xenopus are active at night and inhabit murky water, making it unlikely that vision is used to detect objects at great distances (Elepfandt 1996). Mathis et al (1988) found that Xenopus are hyperopic in water, also indicating that vision is not highly developed for image formation. Little is known about the behavioral development of visual sensitivity in tadpoles over metamorphosis.…”
Section: Role Of Other Sensory Cuesmentioning
confidence: 99%
“…If the LEDs are flashed in sequence, the fundus reflex appears to move in the pupil. Although this procedure proved to be very useful for refracting freely behaving animals (Mathis, Schaeffel & Howland, 1988;Schaeffel & Mathis, 1991;Wagner & Schaeffel, 1991), it is not very useful for a dynamic photorefraction because (1) the resolution of the technique is optimal only for a certain eccentricity and LEDs at that particular eccentricity are only flashed one-fifth of the time, and (2) the edge of the light crescent cannot easily be detected by imageprocessing computer programs because of scattered light in the eye (Hodgkinson, Chong & Molteno, 1991;Schaeffel & Howland, 1991). A program of this kind detects an edge of a light crescent in the pupil even if it is not present because there is always a brightness gradient in the pupil due to the scattered light.…”
Section: Methodsmentioning
confidence: 99%